2013
DOI: 10.1128/aac.01580-12
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Small-Molecule Inhibitor of FtsZ with Superior In Vitro Potency, Drug-Like Properties, and In Vivo Efficacy

Abstract: The bacterial cell division protein FtsZ is an attractive target for small-molecule antibacterial drug discovery. Derivatives of 3-methoxybenzamide, including compound PC190723, have been reported to be potent and selective antistaphylococcal agents which exert their effects through the disruption of intracellular FtsZ function. Here, we report the further optimization of 3-methoxybenzamide derivatives towards a drug candidate. The in vitro and in vivo characterization of a more advanced lead compound, designa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
84
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 43 publications
3
84
0
Order By: Relevance
“…Note that methoxybenzamide derivatives have been shown to be equipotent against susceptible as well as beta-lactam-resistant S. aureus isolates (53). Indeed, we found a very narrow MIC range with similar potencies for MSSA and MRSA isolates, similarly to previous reports.…”
Section: Figsupporting
confidence: 78%
See 1 more Smart Citation
“…Note that methoxybenzamide derivatives have been shown to be equipotent against susceptible as well as beta-lactam-resistant S. aureus isolates (53). Indeed, we found a very narrow MIC range with similar potencies for MSSA and MRSA isolates, similarly to previous reports.…”
Section: Figsupporting
confidence: 78%
“…Prior in vivo study of methoxybenzamide compounds which inhibit FtsZ was limited to a few proof-of-concept studies (14,52,53). In two of these studies, a single dose of the study compound led to improved survival in a murine methicillin-susceptible S. aureus (MSSA) septicemia model, whereas a third study demonstrated a decrease in bacterial burden for a single dose in a murine MSSA thigh model.…”
Section: Figmentioning
confidence: 99%
“…) in vitro, oral activity in infection models, and an acceptable frequency of FtsZ point mutation resistance selection (4.1 Â 10 À9 ) given the evidence for impaired in vitro fitness accompanying the point mutation (Stokes et al 2013). PC190723 also acts synergistically with b-lactam antibiotics against S. aureus, possibly as a result of mislocalization of FtsZ with concomitant disruption of its binding partner (and target of the b-lactams), the PBP bifunctional enzyme(s) (Tan et al 2012).…”
mentioning
confidence: 99%
“…The C5 position of the oxazole moiety can be modified with alkyl, aryl or halogen substituents to achieve higher potency. In this series of compounds, 5-bromo-and 5-chlorooxazolyl analogs exhibit high activity against a mutant strain of S. aureus, G196A [94,95]. To increase the pharmacokinetic parameters of the compounds, polar groups such as alcohol, amine, carboxylic acid and heterocycles were incorporated to the pseudobenzylic position (−CH(R)−O− moiety).…”
Section: Dichamanetin and Its Derivativementioning
confidence: 99%
“…In order to further increase the solubility of compound 18, a prodrug 19 was synthesized. The solubility of 19 was 2-fold higher than its parent compound [94,95] To further increase the pharmacological properties of PC190723, Pilch and coworkers synthesized 1-methylpiperidine-4-carboxamide TXY541 (20, Figure 4), which is a prodrug of PC190723. The compound was effective against MRSA [96].…”
Section: Dichamanetin and Its Derivativementioning
confidence: 99%